Diversified: promoting co-production in course design and delivery - Cumming, Therese M.; Bugge, Aaron Saint-James; Kriss, Karen; McArthur, Ian; Watson, Karin; Jiang, Zixi (Frontiers in Education, 2023)
Neurodivergent students are one of the fastest growing diversity groups in tertiary education. This highlights the need for a Universal Design for Learning (UDL) perspective in course design and delivery. One important component of UDL is student voice, which has been historically lacking, especially for neurodivergent students. In this perspectives article, the authors present a viewpoint on the importance of promoting co-production in course design and delivery between neurodivergent students and instructors and illustrate the concept with examples from the Diversified Project. The “Diversified Group” was established by neurodivergent students and faculty members to address the perceived inadequacy in instructor awareness regarding the varied needs of an expanding neurodiverse student population at the university. The authors provide recommendations for systemic, faculty, school, and instructor-level actions to improve the learning experience for neurodivergent students. Current advances and future directions in promoting co-production in university course design and delivery are provided.